CREATIVE MANIFESTATIONS IN THE GAME OF YOUNG CHILDREN - Reymov Mukhamedali Kengesbaevich; Bazarbayeva Aynura Baxtiyarovna; Valieva Aynura Irshat qizi; Jusipbekova Bayansuluw Timurovna (Scholar Express Journal, 2021)
The subject of this study was the search for elements of creativity in the game of young children
Keywords: Early Childhood; Early Age; Creativity